Application and evaluation of transitory protective stoma in ovarian cancer surgery - He, Jiaqi; Li, Jinke; Fan, Bao; Yan, Liya; Ouyang, Ling (Frontiers in Oncology, 2023)
Ovarian cancer is the most fatal of all female reproductive cancers. The fatality rate of OC is the highest among gynecological malignant tumors, and cytoreductive surgery is a common surgical procedure for patients with advanced ovarian cancer. To achieve satisfactory tumor reduction, intraoperative bowel surgery is often involved. Intestinal anastomosis is the traditional way to restore intestinal continuity, but the higher rate of postoperative complications still cannot be ignored. Transitory protective stoma can reduce the severity of postoperative complications and traumatic stress reaction and provide the opportunity for conservative treatment. But there are also many problems, such as stoma-related complications and the impact on social psychology. Therefore, it is essential to select appropriate patients according to the indications for the transitory protective stoma, and a customized postoperative care plan is needed specifically for the stoma population.